Pengaruh Rasio BOPO, Modal Intelektual, dan Pengungkapan Corporate Social Responsibility Pada Profitabilitas Perusahaan Perbankan - Swendriani, Putu Nesy; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence of the effect of BOPO ratio, intellectual capital, and corporate social responsibility (CSR) disclosure on profitability of banking companies. Research conducted on banking companies on the Indonesia Stock Exchange (IDX) for the 2013-2017 period. The sample is determined through non probability sampling method with purposive sampling technique. The number of samples used in this study were 60 observation samples. The data analysis technique used is the analysis of multiple linear regression analysis. The results of this study indicate that BOPO ratio show a negative effect on profitability of banking companies. The results also show that intellectual capital and CSR disclosure doesn’t affect the probability of banking companies. The research implications theoretically prove stakeholder theory, legitimacy theory, and resource-based theory in explaining the operational efficiency of banking companies. Keywords : BOPO; intellectual capital; CSR; profitability.